2007
DOI: 10.1099/jmm.0.47230-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a clonally different origin of the two cholera epidemics of 2001–2002 and 1980–1987 in South Africa

Abstract: Vibrio cholerae O1 serotype Ogawa and serotype Inaba isolates from the cholera epidemic that occurred in 2001 and 2002 in South Africa were compared with isolates of V. cholerae O1 serotype Inaba from the epidemic that occurred between 1980 and 1987. PFGE using NotI digestion was used to compare stored isolates received during the 1980s epidemic with those received during the epidemic in 2001/2002. A selected number of these isolates were then sequenced to compare the sequence of the wbeT gene in the V. choler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Our recent observation indicates the predominance of serotype Inaba. The serotype switchover from O1 Ogawa to Inaba and vice versa is common in many cholera endemic areas [ 16 ]. Kenyan V. cholerae isolates were resistant for chloramphenicol, streptomycin, sulphonamides, sulfamethoxazole and trimethoprim for isolates from 2007 to 2010 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent observation indicates the predominance of serotype Inaba. The serotype switchover from O1 Ogawa to Inaba and vice versa is common in many cholera endemic areas [ 16 ]. Kenyan V. cholerae isolates were resistant for chloramphenicol, streptomycin, sulphonamides, sulfamethoxazole and trimethoprim for isolates from 2007 to 2010 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in serotype distribution could be a result of serotype switching. Previous studies indicate that serotype switching frequently occurs in the cholera-endemic area as a result of selective pressure due to immunity acquisition during infection [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…From 2007 onwards, trends in molecular subtyping of V. cholerae , started shifting to an increased use of PFGE analysis. In 2007, Keddy and coworkers 56 used PFGE analysis to compare the relatedness of South African V. cholerae O1 isolates from a 2001–2002 epidemic to that of a 1980–1987 epidemic; PFGE analysis showed that isolates from the 1980–1987 epidemic were distinctly different to isolates from the 2001–2002 outbreak. In 2008, Smith and coworkers 57 reported on the first cholera outbreak in Namibia over the period 2006–2007; MDR V. cholerae O1 isolates showed an indistinguishable PFGE pattern and showed resistance to streptomycin, sulphamethoxazole and trimethoprim.…”
Section: Vibrio Choleraementioning
confidence: 99%